Synthesis And Characterization Of Different Polyol Soft Segments In The Preparation Of Palm Kernel Oil Polyol Based Shape Memory Polyurethane - Mohmad Saridi, Mohamad Husaini (Universiti Sains Malaysia, 2018)
Polyurethane-based shape memory polymer (SMPU) is actively investigated to be used in medical applications due to its good biocompatibility and the transition temperature which is closed to the human’s body temperature. In this study, several series of polyols (polycaprolactone (PCL), polyethylene glycol (PEG), polypropylene glycol (PPG) and palm kernel oil-based polyol (PKO-p)) were synthesized with 4,4-methylenebis cyclohexylisocyanate (HMDI), using 1,4-butanediol (BD) as the chain-extender via bulk polymerization synthesis method. The influence of the soft segmentson the mechanical properties and shape-memory behavior of SMPU was investigated. The SMPU was analyzed using different analytical techniques such as Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), Thermogravimetric analysis (TGA), shape memory and tensile testing. The properties of SMPU depend on the molecular weight of soft segment and the amount of hard segment content in soft segment matrix. The result showed that low molecular weight of soft segment show better mechanical properties, whereas the high molecular weight of soft segment produced good shape fixity due to its high crystallinity structure in SMPU. Lastly, PCL-based SMPU showed slightly better tensile properties than PEG-based SMPU and PPG-based SMPU.